«Psychological Figure»: the Image Study - Chunikhina, Svitlana (Psychological Prospects Journal, 2015)
The main approaches to the standardization and interpretation data of drawing methods in psychological researches of the social and political objects are analyzed in paper:«qualitative», «quantitative» and «combined». The first approach is based on the separation of picture’s universal design pattern that allows to interpret its meaning. The second approach is based on the classification of narrative drawings and selection of  typical  methods  of  the  object  image.  In  the  third  approach  «qualitative»  and«quantitative» methods of collecting and interpreting data are used together. The author's approach to the «Psychological figure» data interpretation is proposed in the study of the government officials images. This approach is based on a combination of non- structured data collection methods (drawing, expert interviews) and structured methods of data processing (statistical methods). Nine key categories that determine the design of the images of the bureaucracy are distinguished: a human being– not a human being; government structure; animals; money; positive realism; portraits; geometric shapes; objects; «superhuman» beings. It has been revealed that the main trend in citizens perception is to humanize / dehumanize of government officials. It has been shown that women are significantly more likely to «humanize» the officials, have a generally positive, empathic attitude towards them. Feature of male perception is to dehumanize officials. Men tend to focus on the so-called «mechanics of power»: the system of interaction in the social hierarchy, influence the allocation of resources, the violent nature of power relations. Basic psychological patterns of socio-political perception research areas are designated in the personification of power, on the one hand, and the dehumanization of officials, on the other hand.
Keywords: drawing methods, socio-political perception, dehumanization, perso- nification, the official image